Dissection of binding between a phosphorylated tyrosine hydroxylase peptide and 14-3-3zeta: A complex story elucidated by NMR - Hritz, Jozef; Byeon, In-Ja L; Krzysiak, Troy; Martinez, Aurora; Sklenar, Vladimir; Gronenborn, Angela M (Biophysical journal, 2014)
Human tyrosine hydroxylase activity is regulated by phosphorylation of its N-terminus and by an interaction with the modulator 14-3-3 proteins. We investigated the binding of singly or doubly phosphorylated and thiophosphorylated peptides, comprising the first 50 amino acids of human tyrosine hydroxylase, isoform 1 (hTH1), that contain the critical interaction domain, to 14-3-3?, by (31)P NMR. Single phosphorylation at S19 generates a high affinity 14-3-3? binding epitope, whereas singly S40-phosphorylated peptide interacts with 14-3-3? one order-of-magnitude weaker than the S19-phosphorylated peptide. Analysis of the binding data revealed that the 14-3-3? dimer and the S19- and S40-doubly phosphorylated peptide interact in multiple ways, with three major complexes formed: 1), a single peptide bound to a 14-3-3? dimer via the S19 phosphate with the S40 phosphate occupying the other binding site; 2), a single peptide bound to a 14-3-3? dimer via the S19 phosphorous with the S40 free in solution; or 3), a 14-3-3? dimer with two peptides bound via the S19 phosphorous to each binding site. Our system and data provide information as to the possible mechanisms by which 14-3-3 can engage binding partners that possess two phosphorylation sites on flexible tails. Whether these will be realized in any particular interacting pair will naturally depend on the details of each system.
Keywords: Isoenzymes; peptidy; izotopy fosforu; tyrosin-3-monooxygenasa; Algorithms; nukleární magnetická rezonance biomolekulární; Peptides; 14-3-3 Proteins; fosforylace; Humans; počítačová simulace; molekulární modely; dimerizace; Phosphorus Isotopes; Thermodynamics; termodynamika; Escherichia coli; Nuclear Magnetic Resonance, Biomolecular; izoenzymy; Dimerization; epitopy; Epitopes; vazba proteinů; Computer Simulation; Tyrosine 3-Monooxygenase; Models, Molecular; algoritmy; proteiny 14-3-3; Protein Binding; lidé; Phosphorylation